A randomized-controlled trial pilot study examining the effect of extracorporeal magnetic innervation in the treatment of stress urinary incontinence in women - Weber-Rajek M (Dove Medical Press, 2018)
Magdalena Weber-Rajek,1 Agnieszka Radzimińska,1 Agnieszka Strączyńska,1 Marta Podhorecka,2 Mariusz Kozakiewicz,3 Radosław Perkowski,2 Piotr Jarzemski,4 Kornelia Kędziora-Kornatowska,2 Aleksander Goch1 1Department of Physiotherapy, Collegium Medicum in Bydgoszcz, Nicolaus Copernicus University in Toruń, Toruń, Poland; 2Department of Geriatrics, Collegium Medicum in Bydgoszcz, Nicolaus Copernicus University in Toruń, Toruń, Poland; 3Department of Food Chemistry, Collegium Medicum in Bydgoszcz, Nicolaus Copernicus University in Toruń, Toruń, Poland; 4Clinic of Urology, Collegium Medicum in Bydgoszcz, Nicolaus Copernicus University in Toruń, Toruń, Poland Introduction: Peri- and postmenopausal women frequently suffer from urinary incontinence (UI). Generally, UI becomes more severe with age. It impacts physical, mental, and social functioning as well as the quality of life, often leading to depression. Extracorporeal magnetic innervation (ExMI) is a relatively new conservative treatment method for UI. Objective: The aim of the study was to assess the effectiveness of ExMI in the treatment of stress UI in women. Methods: A total of 52 women were included in the analysis: 28 participants were allocated to the experimental group (EG) and 24 to the control group (CG). The average age was 65.41 years (±SD 4.08). EG patients completed ExMI therapy. The treatment sessions lasted for 15 minutes, and occurred three times a week, for 4 weeks. No therapeutic intervention was applied to the CG. To objectify the treatment outcomes in both groups before and after the treatment, we measured myostatin concentration and performed the UI severity assessment (The Revised Urinary Incontinence Scale), perceived self-efficacy assessment (General Self-Efficacy Scale), and depression severity assessment (Beck Depression Inventory). Results: The authors compared the EG results at the initial and final assessments and found a statistically significant improvement in severity of UI (P=0.001) and depression severity (P=0.006), and a decrease in myostatin concentration (P≤0.001). The authors did not find any statistically significant differences between all measured variables for the CG at the initial and final assessments. Furthermore, there were no statistically significant differences between all measured variables for the EG and the CG at the final assessment. Conclusion: Further trials are needed to determine optimal treatment protocols for various UI types and to evaluate long-term outcomes of the ExMI treatment. Keywords: stress urinary incontinence, Extracorporeal Magnetic Innervation